Effect of Gut Microbiota on the Metabolism of Chemical Constituents of Berberis kansuensis Extract Based on UHPLC-Orbitrap-MS Technique - Du, Huan; Xu, Tong; Yi, Huan; Xu, Xinmei; Zhao, Chengcheng; Ge, Yiman; Zhang, Chuantao; Fan, Gang (Planta Medica, 2021)
The dried stem bark of Berberis kansuensis is a commonly used Tibetan herbal medicine for the treatment of diabetes. Its main chemical components are alkaloids, such as berberine, magnoflorine and jatrorrhizine. However, the role of gut microbiota in the in vivo metabolism of these chemical components has not been fully elucidated. In this study, an ultra-high performance liquid chromatography method coupled with Orbitrap mass spectrometry (UHPLC-Orbitrap-MS) technology was applied to detect and identify prototype components and metabolites in rat intestinal contents and serum samples after oral administration of a B. kansuensis extract. A total of 16 prototype components and 40 metabolites were identified. The primary metabolic pathways of the chemical components from B. kansuensis extract were demethylation, desaturation, deglycosylation, reduction, hydroxylation, and other conjugation reactions including sulfation, glucuronidation, glycosidation, and methylation. By comparing the differences of metabolites between diabetic and pseudo-germ-free diabetic rats, we found that the metabolic transformation of some chemical components in B. kansuensis extract such as bufotenin, ferulic acid 4-O-β-D-glucopyranoside, magnoflorine, and 8-oxyberberine, was affected by the gut microbiota. The results revealed that the gut microbiota can affect the metabolic transformation of chemical constituents in B. kansuensis extract. These findings can enhance our understanding of the active ingredients of B. kansuensis extract and the key role of the gut microbiota on them.
Keywords: Berberis kansuensis; Berberidaceae Gut microbiota; Metabolism; UHPLC-Orbitrap-MS; Traditional Tibetan medicine